2012
DOI: 10.1002/jmv.23424
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus‐associated cerebral sinus vein thrombosis

Abstract: Cytomegalovirus (CMV)-associated thrombosis has been reported many times in the medical literature, and most patients had deep vein thrombosis and/or pulmonary embolism. CMV-associated cerebral sinus vein thrombosis has been reported only twice. We present an immunocompetent patient with CMV-associated cerebral sinus vein thrombosis and no other thrombosis risk factors. This is another example of the pro-thrombotic features of CMV. Physicians should be alert for symptoms and signs of acute CMV infection in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…However, the associated morbidity and mortality have decreased substantially [ 29 ]. Various organisms, e.g., viruses [ [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ], tubercular [ 50 , 51 ], bacteria [ [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] ], protozoa and other parasitic infections [ [60] , [61] , [62] , [63] ] have led to the development of CVT. Infection, when considered to be a direct cause of CVT, can spread from structures either adjacent to dura matter (e.g., paranasal sinuses, nose, mastoid and orbit) or from a distant locus.…”
Section: Resultsmentioning
confidence: 99%
“…However, the associated morbidity and mortality have decreased substantially [ 29 ]. Various organisms, e.g., viruses [ [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ], tubercular [ 50 , 51 ], bacteria [ [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] ], protozoa and other parasitic infections [ [60] , [61] , [62] , [63] ] have led to the development of CVT. Infection, when considered to be a direct cause of CVT, can spread from structures either adjacent to dura matter (e.g., paranasal sinuses, nose, mastoid and orbit) or from a distant locus.…”
Section: Resultsmentioning
confidence: 99%
“…Recognized primarily in immunocompromised patients, such as HIV and renal transplant recipients, CMV mononucleosis has been increasingly recognized as a thrombotic risk factor in immunocompetent patients. To the best of our knowledge to date, there are about 100 case reports, one retrospective case-control, two prospective studies, and one cohort trial reporting local thrombus formation of internal jugular veins, cerebral venous system, and splanchnic, ovarian, iliac, and branch retinal veins [ 3 - 7 ]. The two most common thrombotic events associated with CMV infections are lower-extremity DVT and/or VTE followed by a splanchnic vein thrombosis, such as portal vein thrombosis, superior mesenteric vein thrombosis, inferior mesenteric vein thrombosis, and colic vein thrombosis [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…besides, its usefulness is not proved. 27 Overall, 30.1% of patients whom most of them had viremia, and have been treated with antivirals, that is, ganciclovir and/or valganciclovir, 21 , 164 , 168 , 169 Antiviral Agents have been used in Immunocompromised patients more than immunocompetent patients. 142 Some researchers 27 , 170 have reported that they did not apply anticoagulation therapy in patients with CMV‐associated splenic infarcts; however, their patients also had coagulation disorders, such as heterozygous factor V Leiden.…”
Section: Managementmentioning
confidence: 99%